Analisa Penerapan Sistem pada Hospitality Industry - Haryanto, Steeve (ComTech: Computer, Mathematics and Engineering Applications, 2014)
Analysis on the application of the system hospitality industry aims to determine whether the system from outside has a considerable influence on the number of luxury hotels in Jakarta as well as the factors that influence in picking the hospitality industry service system. The results of this survey are expected to be a consideration in implementing an information system in the field of hospitality industry. The method used in this paper is a literature review and analysis. The initial step in the analysis is to conduct a survey on the current system in hotels in Jakarta, and analysis of the survey results and the identification of the need for local companies to compete with foreign companies. Implementation of the system is no longer measured by how many facilities are available but the system is measured by how stable revenue generated calculations per dayrunning at a hotel with no lost posts.